Case Study: Students’ Achievement In Chemistry, Technology, Engineering and Mathematics (CTEM) at Urban School - Sim Sing Jye; Corrienna Abdul Talib; Faruku Aliyu (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
Since Malaysia  engaged to become a developed country and compete globally, Chemistry, Technology, Engineering, and Mathematics (CTEM) integrated into Malaysia education since the year 2017. This study determined  students’ achievement in CTEM  at urban schools. The Methodology for this study was quasi-experimetal with a sample of 30 students. The instrument used for data collection was test validated by two experts and reliability index of 0.79 was obtained. . The findings showed that the urban students learning CTEM for chemistry topics were still in improvement stage.  It was concluded that learning achievement and  performance  such as critical thinking, creatitivity, problem-solving and innovative skills get improved as the CTEM are continuously integrated into the curriculum of urban schools.